How Bandung Succeeds: Multi-Perspective Study of Determinants of Digital Transformation Success in Public Administration - Ira Meiyenti; Nur Sari Bulan; Astika Ummy Athahirah; Teresa Irmina Nangameka; Mutia Rahmah (Pusjar SKPP Lembaga Administrasi Negara, 2026)
Digital transformation is the main focus in the development of public administration, including in Indonesia. The Electronic-Based Government System (SPBE) implementation at the regional level still faces constraints in human resources, budget, and infrastructure. Bandung City serves as an ideal model of successful SPBE and Smart City implementation. A holistic assessment of the success of digitaltransformation in public administration was performed in this research by combining theoretical approaches (Stakeholder Theory, RBV, and Innovation Diffusion) and practical approaches in the field. This study employed an explanatory sequential mixed methods design, involving 75 quantitative survey respondents and 30 qualitative interview informants at the Bandung City Diskominfo. The data were analyzed using descriptive statistical techniques and thematic analysis. Five key factors, namely (1) Expectations of employees/implementing employees, (2) Expectations of ICT technical operators, (3) Organizational culture, (4) Relative profitability, and (5) Digital leadership were found as the significant factors. The holistic approach successfully integrated multiple theories and field practices in responding to criticisms of previous studies on technical-social focus inequality. The results provide more effective and contextual strategic guidance for local governments to improve the implementation of digital transformation in the public sector.